Management of Blended Learning and Learning Motivation and Student Learning Achievement - Mufti Nawang Prastiko; Juharyanto Juharyanto; Sunarni Sunarni; Maisyaroh Maisyaroh (Universitas Negeri Malang, 2023)
The purpose of the study is to describe; (1) how high is the management of blended learning FIP UM (2) how high is the learning motivation of FIP UM students; (3) how high the learning achievement of FIP UM students is; (4) how is the relationship between blended learning management and learning achievement of FIP UM students; (5) how is the relationship between learning motivation and learning achievement of FIP UM students; and (6) how is the relationship between blended learning management and learning motivation and learning achievement of FIP UM students. This research uses a quantitative approach by utilizing descriptive and correlation analysis methods. This research is located at FIP UM. The population in this study was FIP UM students class of 2019 which amounted to 962 students and a sample of 286 students. The validity test uses pearson moment products while the reliability test uses Cronbach’s alpha. Furthermore, data analysis uses classical assumptions consisting of; (1) normality; (2) linearity; and (3) homogeneity and correlation tests. The results of the study with the use of descriptive and correlation analysis showed various conclusions, namely; (1) FIP UM students have a “Good” perspective on blended learning management; (2) FIP UM students have the motivation to learn with “Very Good” conditions; (3) FIP UM students have learning achievements in the “Praise” qualification; (4) no relationship between blended learning management and learning achievement had a significance value of .738 > 0.05; (5) there is no relationship between learning motivation and learning achievement which has a significance value of .025 > 0.05; and (6) no simultaneous relationship between blended learning management and learning motivation and learning achievement had a significance value of .371 > 0.05.